2019
DOI: 10.1016/j.colegn.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Involving consumers with palliative care needs and their families in research: A case study

Abstract: Background: There are significant policy imperatives to involve consumers at the outset of and throughout research. How best to achieve this in an authentic and meaningful way is elusive, particularly within the palliative care population. Aim: To determine how best to engage people with palliative care needs and their families in co-designing a qualitative study to better understand how to improve care of the dying in the acute care setting. Methods: A case study design informed this work, informed by predete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 21 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…The recruitment process was co-designed with consumer representatives (n = 11) within five panel meetings held over an 18-month period. 38 These panel meetings focused on co-designing optimal strategies for identifying, approaching and recruiting people with palliative Implications for practice, theory or policy? Synthesising identified care priorities into a series of key practice points will enable clinicians and managers to implement care in line with what matters most to people with palliative care needs in the hospital setting; • • Translating identified care priorities into a series of feasible and actionable strategies is critical to inform policy reforms at local, regional and national levels. care needs, and their families, and supporting their participation throughout the proposed research.…”
Section: Recruitmentmentioning
confidence: 99%
“…The recruitment process was co-designed with consumer representatives (n = 11) within five panel meetings held over an 18-month period. 38 These panel meetings focused on co-designing optimal strategies for identifying, approaching and recruiting people with palliative Implications for practice, theory or policy? Synthesising identified care priorities into a series of key practice points will enable clinicians and managers to implement care in line with what matters most to people with palliative care needs in the hospital setting; • • Translating identified care priorities into a series of feasible and actionable strategies is critical to inform policy reforms at local, regional and national levels. care needs, and their families, and supporting their participation throughout the proposed research.…”
Section: Recruitmentmentioning
confidence: 99%
“…Details of this co-design work are detailed elsewhere. 14 The eligibility criteria for this study reflects this advice (Textbox 1).…”
Section: Methodsmentioning
confidence: 99%
“…Study strength’s include the engagement of consumers in co-designing the research protocol, 14 defining the sampling approach, interviewing and data analysis. Co-design enabled broad and representative sampling with similar numbers of people with advanced malignant and non-malignant illness participating.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…16 To date, there have been very few studies that have reported end-users directing their palliative care needs and priorities as a part of service planning. 14,[21][22][23][24][25][26]…”
Section: Introductionmentioning
confidence: 99%
“…Patients, families and carers input can assist service providers to prioritise what services are needed and how they should be provided to achieve the best outcomes. 14 , 15 Applying an approach to service planning that values end-user input, can enable the needs of different population groups to be better understood and optimise patient-centric, holistic, and a stronger relational approach to care. 16 19 …”
Section: Introductionmentioning
confidence: 99%